Perioperative Complications of Cervical Spine Surgery: Analysis of a Prospectively Gathered Database through the Association for Collaborative Spinal Research. (November 2016) - Leckie, Steven; Yoon, S. Tim; Isaacs, Robert; Radcliff, Kris; Fessler, Richard; Haid, Regis; Traynelis, Vincent
Study Design: Retrospective review of prospectively gathered data. Objective: To report the rate and impact of perioperative complications in cervical spine surgery. To our knowledge, no prior study of the cervical spine has analyzed a large prospectively gathered data set for adverse events, based on surgical subgroup. Methods: The ProSTOS database features prospectively documented perioperative adverse events for 1, 269 patients who had cervical spine surgery at multiple centers in North America between 2008 and 2011. We subgrouped patients by approach, whether surgery was a primary or revision operation, and by the number of levels involved. Multivariate analysis with stepwise logistic regression was used to relate complication rates to gender, age, smoking status, body mass index, approach, revision status, and number of levels involved. Follow-up was 41%. Results: Adverse events occurred significantly more frequently in posterior and combined procedures than in anterior procedures. Revision surgery had significantly more complications than primary surgery. For patients who had anterior surgery, those who had one, two, and three or more levels operated had no significant difference in complication rates. Patients who had posterior surgery had significantly more complications if they had two or more levels operated compared with one level. The lowest rates of complications were for one-level primary surgery (<5%), and multilevel posterior, revision posterior, and revision combined surgery had complication rates over 6 times higher (>28%). Patients who had complications were significantly older than patients who did not. The most common adverse events were dysphagia and cardiac complications. The most severe morbid complications, in terms of increased treatment needs and hospital stay, were paraparesis and seizure. Conclusions: Perioperative complication rates in cervical spine surgery are significantly lower in younger patients, surgery performed through an anterior approach (compared with a posterior or combined approach), with fewer levels involved (particularly in posterior surgery), and in primary (compared with revision) procedures.